Sulfur Spillover on Carbon Materials and Possible Impacts on Metal–Sulfur Batteries. Issue 41 (20th September 2018) - Medenbach, Lukas; Escher, Ines; Köwitsch, Nicolas; Armbrüster, Marc; Zedler, Linda; Dietzek, Benjamin; Adelhelm, Philipp
Abstract: There is currently intense research on sulfur/carbon composite materials as positive electrodes for rechargeable batteries. Such composites are commonly prepared by ball milling or (melt/solution) impregnation to achieve intimate contact between both elements with the hope to improve battery performance. Herein, we report that sulfur shows an unexpected "spillover" effect when in contact with porous carbon materials under ambient conditions. When sulfur and porous carbon are gently mixed in a 1:1 mass ratio, complete surface coverage takes place within just a few days along with the loss of the sulfur bulk properties (crystallinity, melting point, Raman signals). Sulfur spillover also occurs in the presence of a liquid phase. Consequences of this phenomenon are discussed by considering a sodium–sulfur cell with a solid electrolyte membrane. Abstract : Liaison between sulfur and carbon : Sulfur and carbon belong to the longest known elements but their interactions might still surprise today. A thus far overlooked phenomenon, referred to as "sulfur spillover", is discussed here. When brought into contact with carbon, sulfur spills over to the carbon surface along with a loss of its bulk properties. These results are particularly relevant for metal–sulfur battery research.